The Importance and Status of Florida Coral Reefs: Questions and Answers - Cory J. Krediet; Kim Ritchie; Max Teplitski (EDIS, 2010)
SL-305, a 5-page illustrated fact sheet by Cory J. Krediet, Kim Ritchie, and Max Teplitski, addresses some questions regarding coral reef biology, coral reef health, and the ecological and economic benefits coral reefs provide. Includes references. Published by the UF Department of Soil and Water Sciences, August 2009.